2009
DOI: 10.1074/jbc.m109.031419
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimerization of the Sialidase NEU1 with the Chaperone Protective Protein/Cathepsin A Prevents Its Premature Oligomerization

Abstract: Lysosomal neuraminidase-1 (NEU1) forms a multienzyme complex with ␤-galactosidase and protective protein/cathepsin A (PPCA). Because of its association with PPCA, which acts as a molecular chaperone, NEU1 is transported to the lysosomal compartment, catalytically activated, and stabilized. However, the mode(s) of association between these two proteins both en route to the lysosome and in the multienzyme complex has remained elusive. Here, we have analyzed the hydrodynamic properties of PPCA, NEU1, and a comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 54 publications
3
75
0
Order By: Relevance
“…The reason(s) for this inhibitory potency of Tamiflu on Neu1 and Neu4 sialidase activity in live BMC-2 macrophage cells is unknown. For Neu1, however, it may be due to its unique orientation with the molecular multi-enzymatic complex that contains β-galactosidase and cathepsin A [15,[53][54][55]60] and elastinbinding protein (EBP) [56], the complex of which would be associated within the ectodomain of TLR receptors [8]. Since Neu4 is not associated with other proteins for enzymatic activity [19], we think that Tamiflu might have unique inhibitory effects specifically for Neu1 and Neu4 sialidase activity.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The reason(s) for this inhibitory potency of Tamiflu on Neu1 and Neu4 sialidase activity in live BMC-2 macrophage cells is unknown. For Neu1, however, it may be due to its unique orientation with the molecular multi-enzymatic complex that contains β-galactosidase and cathepsin A [15,[53][54][55]60] and elastinbinding protein (EBP) [56], the complex of which would be associated within the ectodomain of TLR receptors [8]. Since Neu4 is not associated with other proteins for enzymatic activity [19], we think that Tamiflu might have unique inhibitory effects specifically for Neu1 and Neu4 sialidase activity.…”
Section: Discussionmentioning
confidence: 91%
“…Since Neu1 sialidase is also a lysosomal enzyme, which has a unique orientation with the molecular multienzymatic complex that contains β-galactosidase and cathepsin A [15,[53][54][55] and elastin-binding protein (EBP) [56], we have recently shown that Neu1 and not Neu2, -3 and -4 forms a complex with TOLL-like receptors -2, -3 and -4 on the cell surface of naive macrophage cells [8]. The data provide evidence for a membrane controlling mechanism that is initiated by ligand binding to TLR-2, -3 and -4 to induce Neu1 sialidase activity within minutes in live primary bone marrow (BM) macrophage cells and macrophage and dendritic cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the tertiary structure of NEU1 and its complex with CathA and Gal is still unknown, the mechanism of NEU1 enzymatic activation in the complex remains mainly unclear. Recently, Bonten et al studied the interaction between the soluble recombinant NEU1 and CathA expressed in insect cells and showed that in the absence of CathA, NEU1 self-associates into inactive chain-like oligomers [45]. CathA presumably competes with NEU1 for the same binding site and can reverse the selfassociation of NEU1 by causing the disassembly of NEU1 oligomers and the formation of 102 kDa CathA-NEU1 heterodimers [45].…”
Section: Mammalian Neuraminidase 1 (Neu1) and Its Catabolic Rolementioning
confidence: 98%
“…Recently, Bonten et al studied the interaction between the soluble recombinant NEU1 and CathA expressed in insect cells and showed that in the absence of CathA, NEU1 self-associates into inactive chain-like oligomers [45]. CathA presumably competes with NEU1 for the same binding site and can reverse the selfassociation of NEU1 by causing the disassembly of NEU1 oligomers and the formation of 102 kDa CathA-NEU1 heterodimers [45]. The authors, however, did not observe further association of these heterodimers into high-molecular weight complexes, suggesting that the interaction between the recombinant forms of CathA and NEU1 can be different from that occurring in the cell.…”
Section: Mammalian Neuraminidase 1 (Neu1) and Its Catabolic Rolementioning
confidence: 99%
“…Neu1, Neu2 and Neu3 show enzyme activity on the extracellular membrane surface. Neu1 specifically acts on low-molecular-weight substrates, including 4MU-Neu5Ac, oligosaccharides and glycopeptides (6,7). Neu1 is mainly located at lysosomes.…”
Section: A Introduction S I a L I D A S E R E M O V E S S I A L I C mentioning
confidence: 99%